THE INFLUENCE OF COORDINATION AND SUPERVISION ON EMPLOYEE PERFORMANCE AT THE REGIONAL REVENUE MANAGEMENT UPTD (PPD) BALARAJA BANTEN PROVINCE - Purwaningsih, Nining; Anggraini, Adella Putri (Jurnal Comparative: Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of Coordination and Supervision on Employee Performance, both partially and simultaneously at UPTD Regional Revenue Management (PPD) Balaraja, Banten Province. This study uses a quantitative approach method. The sample was taken as many as 64 employees. The sampling technique uses NonProbability sampling using Saturated Sampling. The data management is assisted by using the Microsoft Excel application and Spps Software version 25. The results showed that partially Coordination (X1) had a positive and significant effect on Employee Performance with a t count of 9.529 > t table of 1.998 and a sig value of 0.000 <0.05. As for Supervision, it has a positive and significant effect on Employee Performance with a t count of 8.138 > t table of 1.998 and a sig value of 0.000 > 0.05. Simultaneously it shows that Coordination (X1), Supervision (X2) on Employee Performance by having f count 50.771 > f table 3.15 and sig. 0.000 < 0.05. The results showed that there was an effect of Coordination and Supervision on Employee Performance with the value of the multiple regression equation Y = 5.863 + 0.549 X1 + 0.312 X 2+ eKeywords: Coordination; Supervision; Employee Performance